Speech by Mr. Timothy Sadera - President, Embu Universitycollege Students Association - Sadera, Timothy (My University, 2015)
Speech by Mr. Timothy Sadera - President, Embu Universitycollege Students Association During The Embu University College ISO 9001-2008 Certification Celebrations And Launch Of Strategic Plan Held On 23rd March 2015